Structural and Population Polymorphism of RT-Like Sequences in Avian Schistosomes Trichobilharzia szidati (Platyhelminthes: Digenea: Schistosomatidae) - Yesakova, A. P.; Guliaev, A. S.; Chrisanfova, G. G.; Semyenova, S. K.; Ryskov, A. P. (BioMed research international, 2015)
Recently we developed the genus-specific markers of the avian schistosomes of the genus Trichobilharzia, the causative agents of human cercarial dermatitis. The 7 novel genome sequences of T. franki, T. regenti, and T. szidati revealed similarity with genome repeat region of African schistosome Schistosoma mansoni. In the present work we analyzed the 37 new T. szidati sequences to study intragenome variability and host specificity for the parasite from three localities of East Europe. DNAs were isolated from cercariae or single sporocysts obtained from 6 lymnaeid snails Lymnaea stagnalis and L. palustris from Belarus and Russia. All sequences formed three diverged groups, one of which consists of the sequences with multiple deletions; other groups involved two paralogous copies with stop codons and frameshift mutations. Strong association between geographical distribution and snail host specificity cannot be established. All studied sequences have homology with the reverse transcriptase domain (RT) of Penelope-like elements (PLE) of S. mansoni and S. japonicum and new members of RT family were identified. We proposed that three diverged groups RT sequences of T. szidati are results of duplication or transposition of PLE during parasite evolution. Implications of the retroelement dynamics in the life history of avian schistosomes are discussed.